Early stages of particle formation by in-situ UV-vis and HRS - Peukert, Wolfgang; Segets, Doris; Schürer, Benedikt (technical proceedings of the 2010 NSTI Nanotechnology Conference and Expo, 2010)
We present a new approach for the study of early states of particle formation that can be applied for precipitation processes that occur on timescales from milliseconds to several minutes. A T-shaped micro-mixer is used to precipitate nanoparticles at steady state conditions. The nucleation and growth of the nanoparticles occurs along the path through a transparent quartz capillary. Hyper Rayleigh scattering (HRS) and UV/Vis absorbance spectra are recorded simultaneously. By changing the measurement position along the capillary, different reaction stages of the nanoparticle formation process can be studied in detail. As the precipitation is performed at steady state the integration time for recording signals is not limited by the kinetics of the precipitation process. The HRS intensities and the particle size information can be used to calculate the nucleation and growth rates of the particle formation process.
Keywords: Hyper Rayleigh Scattering; Nanoparticle; Precipitation; UV-Vis; ZnO